Cold agglutinin disease and COVID-19 requiring therapeutic plasma exchange. Issue 7 (26th July 2021) - Ahmed, Yousuf; Khandelwal, Aditi; Walker, Laura
Abstract : A 70-year-old man with known cold autoimmune haemolytic anaemia was referred to the emergency department with increased shortness of breath on exertion. He had been confirmed positive for non-variant COVID-19 infection 1 week earlier based on nasopharyngeal swab PCR assay. CT thorax demonstrated diffuse patchy bilateral ground glass opacities, consistent with COVID-19 pneumonia. Bloodwork demonstrated severe cold agglutinin mediated haemolytic anaemia. To help stabilise the patient, he was transferred to a tertiary care hospital for urgent therapeutic plasma exchange. Key supportive therapy included folic acid supplementation, ensuring the patient was kept warm and warmed infusions including transfusions via the apheresis machine. The patient made a good recovery following plasma exchange, and his haemoglobin levels remained stable by discharge.